Mathematics and curriculum development (2017)
The unprecedented changes that are taking place in today's world will profoundly affect the future of today's students. To meet the demands of the world in which students will live, students will need knowledge of mathematics to adapt to changing conditions and to learn independently. Mathematics is the abstract study of topics such as quantity (numbers), structure, space and change. Major development in mathematics education in this millennium has been the increased amount of mathematics that all citizens are expected to know. Today’s mathematics curriculum must prepare students for their future roles in society by equiping them with essential mathematical knowledge and skills of reasoning problem solving communication and most importantly, with the ability and the incentive to continue learning on their own. This paper focuses on the mathematics and curriculum development which includes what is mathematics, mathematics processes, curriculum and curriculum development, processes of planning and development of curriculum. Problems and prospects of mathematics teaching in Nigeria secondary schools were also discussed, while recommendations were provided.